Doutrina do duplo efeito: fenômeno moral dialogando com Aristóteles, Tomás de Aquino e os contemporâneos sobre a doutrina do duplo efeito. - Aguiar, Roberto Múcio Bezerra de (2022)
This is the Doctrine of the Double Effect – DDE. Developed by Thomas Aquinas in the medieval period, consist of the manifestations of licit reactive human actions can produce double consequences, containing a positive and a negative part. Negative effects (side effects), however, must be tolerated by the morality. The doctrine is focused on the thesis of self-defense aimed at solving conflicts of interest motivated by individual actions, being extended to collective conflicts based on the values of justice and equity. The touchstone of the research concerns the negative consequences in the manifestations of human actions and their validation conditions, arguing that in conflicts of individual or collective interest the action has a defensive nature; that is free and intentional, lawful and proportionate, causing – when possible – the least amount of damage to the aggressor. The research was deepened from the studies of Acrasia in Aristotle, as well as in Theory and classification of actions in Donald Davidson, also emphasizing the intellectual maturity of the human person according to Moral Consciousness and Communicative Action in Habermas. The doctrine was extended to the solution of conflicts of collective interests, according to the perspective of John Rawls, adopting the foundations of the Theory of Equitable Social Justice as a criterion of equity.